Effects of Pesticides and Fertilizers on Groundwater Quality Using Geophysics and Physiochemical Analysis in Oko-Efo, Lagos State University, Ojo (LASU) - Whetode, James; Anko, Senami; Adegbola , Rafiu; Musa, Buba; Mutalib Hammed , Ayofe (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2024)
Modern agriculture use pesticides and fertilizers to improved agricultural production, increasing yield, ensuring food access and reducing the ongoing danger of plant-pathogen infections. However, indiscriminate use of pesticides and fertilizers harms the environment and human health, resulting in soil loss and nutritional imbalances. This study investigated the potential effects of pesticides and fertilizer on groundwater in Oko-Efo, LASU. An electrical resistivity survey using Three (3) Horizontal profiling and Twelve (12) Vertical Electrical Sounding (VES) points was done and physiochemical analysis to study groundwater pollution due to pesticides and fertilizers used by farmers. The results suggest possible geoelectric layers in the study location: Topsoil, Clayey sand, Sand and Saturated sand. The topsoil composed of conglomerate with resistivity ranging from 323 – 666 Ωm upto the depth of 5 m which is suspected to be polluted. Water samples were collected at an average depth of 3 m and the physiochemical analysis further justified the presence of contamination as dissolved oxygen (DO), pH and electrical conductivity (EC) are above WHO standards. It is therefore recommended that the use of pesticides and fertilizers are regulated to prevent groundwater contamination.